Strategic Management and Digital Transformation: A Systematic Review of Organizational Transformation Frameworks (2019–2024) - Rani Anwar; Satria Bangsawan; Ayi Ahadiat (AIBPM Publisher, 2025)
Digital transformation has become a key strategic agenda for organizations facing technological disruption and increasing environmental complexity. However, existing frameworks remain fragmented and lack integration with strategic management perspectives. This study aims to synthesize organizational transformation frameworks developed between 2019 and 2024 to support digital strategic management. Using a systematic literature review guided by the PRISMA 2020 protocol, 50 Scopus-indexed articles were analyzed through a structured selection process. The findings show that contemporary frameworks are multidimensional, typically comprising technology integration, leadership, culture, dynamic capabilities, and process transformation. People-first approaches, digital leadership, and digital maturity emerge as critical success factors. Additionally, an increasing trend highlights the integration of digitalization and sustainability through twin transformation models. This study concludes that successful digital transformation depends on aligning organizational capabilities with context-specific frameworks, offering both theoretical contributions and practical guidance for designing adaptive, evidence-based transformation strategies.